Perancangan dan Analisis dari Automation Gasket Assembling Machine untuk Pengurangan Jumlah Tenaga Kerja - Muhammad Ekka Januar Akbar; Joni Welman Simatupang (JIE Scientific Journal on Research and Application of Industrial System, 2018)
Manufacturing process need lot of man power for assembling parts process, but every year minimum of basic salary for man power always increase, however price product to customer increase not significant same as basic salary increase. Therefore management must think how to solve this problem, because if there is no counter measure profit, the company will face loss. There are at least three ways to counter measure this condition: first is by changing manual process for part assembling using automation system, second is to get the import parts from local supplier, and third is change import consumable tool to local supplier. This paper will explain about the process and impact of changing manual proses in gasket part assembling to full automatic gasket part assembling with new automatic machine. This machine using programmable logic controller (PLC), where all process which was done by man power will change to mechanical structure, so this process will change to automatic process. At the end, this process can reduce the need for man power and give effect to the reduction of direct labor cost also to be about 9,2 million rupiah in one shift production/month, however this nominal will fluctuate due to the number of total production quantity/month. Anothe effect with the use of automatic machine for quality process level is the increase of product quality level development because all item process check will be done by 100% sensor check, so the human error factor will be eliminated by using full automatic gasket assembling machine.Keywords: Increasing of salary, average minimum salary, Automation process, man power reduction, decreased of direct labor cost, PLC system control.